2020
DOI: 10.1097/dcr.0000000000001888
|View full text |Cite
|
Sign up to set email alerts
|

Size Criteria Is Not Sufficient in Selecting Patients for Local Excision Versus Radical Excision for Rectal Neuroendocrine Tumors >2 cm: A National Cancer Database Analysis

Abstract: BACKGROUND: Patients with rectal neuroendocrine tumors >2 cm often undergo radical surgery, despite limited data supporting this practice. Five- and 10-year survival rates for these patients have been reported previously as 74.8% and 58.6%. OBJECTIVE: Overall survival was compared between local excision and radical surgery and pN0 and pN1 within the radical surgery subgroup for rectal neuroendocrine tumors >2 cm. Factors independently associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Many studies have confirmed that the possibility of LNM in tumors measuring less than 1 cm is extremely low and that 10%-15% tumors measuring 1-2 cm have LNM and 60%-80% tumors measuring greater than 2 cm have LNM. 17,18 However, a study Izquierdo et al 19 including 356 cases of RNETs showed that there may be a subgroup of patients for which local resection can be performed among patients with RNETs measuring greater than 2 cm. The feasibility of local resection can be determined based on the LNM status and tumor grade.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have confirmed that the possibility of LNM in tumors measuring less than 1 cm is extremely low and that 10%-15% tumors measuring 1-2 cm have LNM and 60%-80% tumors measuring greater than 2 cm have LNM. 17,18 However, a study Izquierdo et al 19 including 356 cases of RNETs showed that there may be a subgroup of patients for which local resection can be performed among patients with RNETs measuring greater than 2 cm. The feasibility of local resection can be determined based on the LNM status and tumor grade.…”
Section: Discussionmentioning
confidence: 99%